Regenerative Protocol for Ligamentous Defects in Patients with Sinus Tarsitis: A Case Series - Parker, Robert; Shou, John; Woods, Crislyn; Lambert, Naomi; Barrett, Tyler (Archives of Clinical and Biomedical Research, 2025)
Heel pain in the “funnel-shaped” space between the calcaneus, talus, and talocalcaneonavicular and subtalar joints may be representative of Sinus Tarsi syndrome. The pain is often characterized by a burning, numbness, or tingling sensation that can stem from strains and tears in the ligaments in that area. Injury treatment typically includes balance training, muscle exercises, bracing, foot orthosis, and non-steroidal antiinflammatory drugs (NSAIDs). This study presents a regenerative protocol highlighting extracorporeal pulse-activated therapy (EPAT), Wharton Jelly (WJ) tissue allografts, laser therapy, and orthotics as an alternative intervention for patients who fail standard-care treatments. WJ replaces damaged tissue, unlike other therapies, which aim to reduce swelling and symptomatic pain. This study includes five female patients who have previously failed standard-of-care treatment. After an average of 80 days, the cohort reported an overall 85.29% improvement in pain. The study's limitations include a small cohort size and a non-blinded design. Given the significant improvement in pain, WJ tissue allograft, combined with other techniques, presents a promising patient care plan for tissue defects associated with Sinus Tarsi syndrome when standard-of-care treatments fail. These results provide preliminary evidence for a more extensive, randomized study to define dosage protocols further and confirm safety and efficacy.